Integrated molecular-morphologic meningioma classification: a multicenter retrospective analysis, retrospectively and prospectively validated - Maas, Sybren L. N.; Stichel, Damian; Hielscher, Thomas; Sievers, Philipp; Bergmeister-Berghoff, Anna Sophie; Schrimpf, Daniel; Sill, Martin; Euskirchen, Philipp; Blume, Christina; Patel, Areeba; Kardo, Helin; Reuss, David; et al. (Journal of clinical oncology, 2021)
Meningiomas are the most frequent primary intracranial tumors. Patient outcome varies widely from benign to highly aggressive, ultimately fatal courses. Reliable identification of risk of progression for individual patients is of pivotal importance. However, only biomarkers for highly aggressive tumors are established (CDKN2A/B and TERT), whereas no molecularly based stratification exists for the broad spectrum of patients with low- and intermediate-risk meningioma.